UPAYA MANAJEMEN MASJID DALAM MENINGKATKAN AKTIVITAS KEAGAMAAN DI MASJID DARUSSALAM KELURAHAN IRINGMULYO KECAMATAN METRO TIMUR KOTA METROTAHUN 2021 - Ramadany, Anwar Aldy; Songidan, Junaidi; Rohman, Fathur (Universitas Muhammadiyah Metro, 2021)
The mosque is a place of prostration, besides that the mosque also functions as a place to carry out various religious activities. The formulation of the problem in this study is to find out how mosque management is to improve religious activities and the factors that inhibit and support activities. The purpose of this study was to determine the management of the mosque and to determine the inhibiting and supporting factors in increasing religious activities at the Darussalam Mosque, Iringmulyo sub-district, East Metro district. The data collection method that the researcher uses is the method of observation, interview, and communication. The data were analyzed by sorting the available data, then presented systematically and drawing conclusions. Based on the results of the study, it is known that the management of the Darussalam mosque in increasing religious activities is quite good, the management has established an organizational structure, carries out management functions and makes programs clearly. The inhibiting factors for the program, namely the COVID-19 pandemic and the lack of budget funds, in activities are supported by managers who are experts in their fields and are supported by many religious leaders. The conclusion in this study is that mosque management in increasing religious activities has been going well with the implementation of the management function or mosque rites and the manager is still trying to realize religious activities even in the Covid-19 pandemic condition and supported by religious leaders and the community around the Darussalam mosque.